Un nuevo hospedero del periquito del aguacate, metcalfiella monogramma (germar) (hemiptera: membracidae), en México - Romero Nápoles, Jesús; D. Koch, Stehpen; Carrillo Sánchez, José Luis; Valdéz Carrasco, Jorge M. (Instituto de Ecología, A.C., 2011)
A new host plant for Metcalfiella monogramma (Germar) is recorded, the maple tree Acer negundo subsp. mexicanum (DC.) Wesm. (Aceraceae), moreover some biological observations about the insect and its new host are given.